Iron metabolism modulation in Atlantic salmon infested with the sea lice Lepeophtheirus salmonis and Caligus rogercresseyi: A matter of nutritional immunity? - Valenzuela-Muñoz, Valentina; Gallardo-Escárate, Cristian Jorge (2021)
Sea lice are copepodid ectoparasites that produce high economic losses and environmental issues, thus impacting the salmon aquaculture worldwide. Atlantic salmon (Salmo salar) from Northern and Southern Hemispheres are primarily parasitized by Lepeophtheirus salmonis and Caligus rogercresseyi, respectively. To cope L. salmonis infestation, studies suggest that Atlantic salmon can restrict iron availability as a mechanism of nutritional immunity. However, no molecular studies of iron regulation from salmonids infected with C. rogercresseyi have been reported. The aim of this study was to determine if there are differences in the regulation of iron metabolism in Atlantic salmon infested with L salmonis or C. rogercresseyi. For comparisons, skin and head kidney were profiled using qPCR of 15 genes related to iron regulation in Atlantic salmons infected with each sea louse species in Norway and Chile, respectively. Prior to infestation, no significant differences were observed between fish group. However, genes involved in iron transport and Heme biosynthesis were highly upregulated in Atlantic salmon infested with L salmonis. Interestingly, hepcidin and Heme oxygenase, a component of the Heme degradation pathway, were upregulated during C. rogercresseyi infestation. Oxidative stress related genes were also evaluated, showing higher transcription activity in the head kidney than in the skin of Atlantic salmon infested with L salmonis. These comparative results suggest pathogen-specific responses in infected Atlantic salmon, where iron metabolism is primarily regulated during the infestation with L salmonis than C. rogercresseyi. Feeding behavior, for instance haematophagy, of the infesting sea lice species in relation to iron modulation is discussed. (C) 2016 Elsevier Ltd. All rights reserved. Regular 2015 FONDECYT FONDECYT